Experimental research on helicopter tail shake phenomenon - Ishak, Iskandar Shah; Mansor, Shuhaimi; Mat Lazim, Tholudin (2008)

(untitled)
Helicopter tail shake phenomenon is still remained as a long dragged issue that adversely affected the overall performance, occupants’ comfortness and handling qualities of helicopter. This problem is more severe in modern helicopter as it needs to fly faster and with high manoeuvrability, causing rigorous interactional aerodynamic (I/A) related vibration problems. The objective of this present research is to improve basic understanding of the viscous unsteady flow phenomenon observed behind the helicopter tail part. A good understanding of this matter is necessary as a typical aspect of tail shake that it has unsteady random character, indicating that the wake induced excitation is in also unsteady of nature. For this, a wind tunnel test had been conducted with a rigid 14% model of generic Eurocopter 350Z helicopter in the Universiti Teknologi Malaysia – Low Speed Tunnel (UTM-LST) with a test section size of 2m x 1.5m x 5.8m and 288 km/hr maximum test wind speed. The model, supplied by Eurocopter France, is equipped with a motor that can rotate the main rotor up to 900 rpm during wind-on condition. Therefore, the wake analysis can be done ‘with’ or ‘without’ main rotor rotation which undoubtly can give a more comprehensive understanding on the wake induced. As the induced wake, which consequently causing tail to shake, differs with pitch and yaw angle, the wind tunnel test was performed in a range of -10o to +10o of pitch and yaw angle, respectively. The selected test wind speed was 40 m/s, which corresponds to a Reynolds number of 3.7 x 106. To investigate the characteristics of the induced wake, a mapping process was done at 3 different planes behind the model with each plane consists of 4 measurement points. With this, it is hope the collected data could help on the wake analysis that contributes to helicopter tail shake phenomenon. DANTEC single hotwire, type 55P01, was used to determine local turbulence level and velocity at each respectively point throughout all the tests. However, only static results and analysis will be discussed in this paper.